Pengaruh Sedimentasi Terhadap Fungsi Kapasitas Saluran Drainase di Jalan Tongkol Kelurahan Seketeng Sumbawa Besar - Dwianti, Novia; Mawardin, Adi; Kurniati, Eti (Journal of Applied Civil Engineering and Infrastructure Technology, 2023)
Population growth is always followed by changes in land use. These changes mean that the land surface can no longer absorb rainwater naturally, creating a high runoff coefficient and affecting erosion rates. Rainwater is channeled into the drainage along with erosion material. The increased sedimentation process causes silting of the channel which results in a decrease in drainage capacity. The purpose of this study is to determine the characteristics of sediment by grain size analysis method and the results of grain diameter range from 1.062 mm to 1.506 mm, categorized as very coarse sand with specific gravity (ρs) of 0.00239 kg/m3. Knowing the Bed load Transport Rate with the Meyer-Petter and Muller Method which is around 1.714×103 m3/year. Knowing the rate of suspended load transport using the USBR (United States Beureu Reclamation) Method which is 0.0443 tons/year. As well as knowing the percentage of sediment to the Tongkol street drainage channel along the research location of 74.46% and categorized as severely damaged. The recommended action that can be taken is rehabilitation. Drainage channel rehabilitation can be done by dredging sediment, as well as repairing damaged channel construction by CL Directorate General of Natural Resources Men PU No. 02 / SE / 2011.